In vitro biocompatibility and cellular interactions of a chitosan/dextran‐based hydrogel for postsurgical adhesion prevention. Issue 2 (29th May 2014) - Aziz, Manal A.; Cabral, Jaydee D.; Brooks, Heather J. L.; McConnell, Michelle A.; Fitzpatrick, Clare; Hanton, Lyall R.; Moratti, Stephen C.
Abstract In this paper, we report the in vitro biocompatibility and cellular interactions of a chitosan/dextran‐based (CD) hydrogel and its components as determined by mutagenicity, cytotoxicity, cytokine/chemokine response, and wound healing assays. The CD hydrogel, developed for postsurgical adhesion prevention in ear, nose, and throat surgeries, was shown by previously published experiments in animal and human trials to be effective. The hydrogel was synthesized from the reaction between succinyl chitosan (SC) and oxidized dextran (DA). Cytotoxicity was assessed in an xCELLigence system and cytokine/chemokine responses were measured by ELISA in human macrophage, nasopharyngeal epithelial, and dermal fibroblast cells. A wound healing model utilized nasopharyngeal epithelial cells. CD hydrogel and DA were nonmutagenic in the Ames test. CD hydrogel showed moderate cytotoxicity for the cell lines, DA being the cytotoxic component. Some inhibition of wound healing occurred due to the cytotoxic nature of DA. Cells cultured with CD hydrogel showed no increase in TNF‐α, IL‐10, and IL‐8 levels. It is hypothesized that the cytotoxicity of DA is moderated when reacted with SC and that CD hydrogel inhibits unwanted fibroblastic invasion preventing scarring and adhesions. Together with the previously published human and animal trial data, the results indicate CD hydrogel is biocompatible in the setting of endoscopic sinus surgery. This work represents the first study of CD hydrogel with human cell lines and provides essential information for its future application in biomedicine. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 332–341, 2015.